Platypeplus aprobola (Meyrick) (Lepidoptera-Olethreutidae), a Leaf Roller on Moghana macrophylla (Wild) O.KTZE - Kulkarni, S. M.; Malhotra, C. P.; Ghosh, M. (Indian Forester, 1967)
Ptarypeplus aprobola (Meyr.) in its larval stage attack the top leaves of the shoots of M.macrophylla and check the growth of the bushes. The maximum infestation was found during the first half of August when 5-6 larvae per bush were recorded and 10-12% of shoots were found damaged during the year 1961. During the period August to December preovlposition and Incubation periods last on an average for 2.92 to 3.23 days and 3 to 4.31 day. Respectively. There are five larval instars and the larval period varies from 11 to 18.66 day. Whereas pupal period ranges from 7.61 to 23.57 days. Longevity of adults when fed on 5% sugar solution came to 6 to 7 days. The total life. Cycle is completed in 21.6 days during August to September and 46.5 day. During October to December.